Comparison of standardised mortality ratios for renal failure before and after the 2011 Great East Japan Earthquake and Tsunami: an analysis of national vital statistics. Issue 12 (28th December 2018) - Tsukinoki, Rumi; Murakami, Yoshitaka; Kawado, Miyuki; Hashimoto, Shuji
Abstract : Objective: The impact of the 2011 Great East Japan Earthquake on renal failure (RF) risk remains unclear. We examined the 1-year impact of this disaster on RF mortality. Setting: This ecological study focused on the year before and after the earthquake. The data sources were national vital statistics (2010–2012), the national census (2010) and the Basic Resident Registration (2010–2012). Participants: Our study included all residents in Iwate, Miyagi and Fukushima, 1 year before and after the earthquake. Primary and secondary outcome measures: We calculated standardised mortality ratios (SMRs) for RF, chronic RF and acute RF. Postearthquake weekly SMRs were calculated using the number of RF deaths for the corresponding weeks in 2010 as a reference. The SMRs for RF were compared between the coastal and inland municipalities using kernel-weighted polynomial smoothing. Results: There were 1290 RF deaths in the three prefectures during the year after the earthquake (chronic RF: 804 and acute RF: 236). The SMR for RF increased significantly in the first week after the earthquake in coastal areas (3.11; 95% CI: 1.84 to 4.37), but did not increase in inland areas (0.93; 95% CI: 0.47 to 1.38). A similar trend was observed for chronic RF (coastal: 4.0; 95% CI: 2.0 to 6.0; inland: 1.1; 95% CI: 0.4 to 1.7). SMRs for RF and chronic RF decreased over time and reached 1.0 approximately 20 weeks after the disaster. Changes in SMRs for acute RF were not apparent due to the low number of deaths. Conclusions: Mortality due to RF and chronic RF, but not acute RF, increased in coastal areas after the earthquake. Chronic RF may have been exacerbated by disaster-induced sympathetic activation and poor management of renal dysfunction. Increased hypertension and damage to essential infrastructure and medical equipment may also have increased mortality in people with kidney disease.